Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/ajt.14223
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Ureteric Stents in Renal Transplant Recipients: A Multicenter Randomized Controlled Trial of Early Versus Late Removal

Abstract: Prophylactic ureteric stenting in renal transplantation reduces major urological complications; however, morbidity is related to the indwelling duration of a stent. We aimed to determine the optimal duration for stents in this clinical setting. Patients (aged 2-75 years) from six UK hospitals who were undergoing renal transplantation were recruited and randomly assigned to either early stent removal at 5 days (without cystoscopy) or late removal at 6 weeks after transplantation (with cystoscopy). The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 8 publications
(11 reference statements)
0
49
0
3
Order By: Relevance
“…A recent meta‐analysis on the current practice of ureteric stent removal found that removal within 3 weeks after transplantation is associated with a significant reduction in UTIs without risking an increased incidence of MUCs 17 . Our multi‐centre randomized controlled trial on the optimal duration for stents in pediatric and adult renal transplantation (TrUST trial—ISRCTN09184595) found that removing stents early (at 5 days) rather than later (at 6 weeks) significantly reduced the rate of stent‐related complications 26 …”
Section: Discussionmentioning
confidence: 85%
“…A recent meta‐analysis on the current practice of ureteric stent removal found that removal within 3 weeks after transplantation is associated with a significant reduction in UTIs without risking an increased incidence of MUCs 17 . Our multi‐centre randomized controlled trial on the optimal duration for stents in pediatric and adult renal transplantation (TrUST trial—ISRCTN09184595) found that removing stents early (at 5 days) rather than later (at 6 weeks) significantly reduced the rate of stent‐related complications 26 …”
Section: Discussionmentioning
confidence: 85%
“…In the late removal group, stent‐related complications, especially UTIs, were significantly more frequent. These indicate that early removal reduces significantly stent‐related complications . In several studies, stenting is identified as an independent risk factor of another infectious complication, that is BK virus nephropathy .…”
Section: Discussionmentioning
confidence: 95%
“…These indicate that early removal reduces significantly stent-related complications. 27 In several studies, stenting is identified as an independent risk factor of another infectious complication, that is BK virus nephropathy. 28,29 In all studies reporting this association, stenting was performed with an indwelling (JJ) catheter.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomised controlled trial confirmed that early stent removal on Day 5 significantly reduced stent-related complications and improved quality of life in the first three months after transplantation. (8) A Cochrane review by Wilson et al, (7) including 1,154 patients, found that patients who had ureteric stents developed more complications of haematuria, irritative symptoms and stent-related pain. Significantly, two grafts were lost as a result of stent-related infectious complications and pooled results also indicated a general increased risk of urinary tract infection with the use of stents.…”
Section: Discussionmentioning
confidence: 99%